Kapabilitas Pemasaran dalam Meningkatkan Kinerja Pemasaran pada Coffee Shop - Suciati, Famela Sophya; Danial, R. Deni Muhammad; Ramdan, Asep Muhamad (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to determine the effect of marketing capabilities in improving marketing performance. The method in this research uses a quantitative method with an associative approach. This research uses a sample of 37 coffee shops with the owner being the respondent. The technique in order to collect a number of data used for this research is primary data, namely observation, interviews and questionnaires and secondary data used is literature study. This research conducts testing to determine the valid and reliable data used. The technique to process a number of data is done using the correlation coefficient test, the coefficient of determination test, the simple linear regression test and the hypothesis test used is the significance test (T test). The conclusions of this research indicate that there is a significant influence of the marketing capability variable on marketing performance.